Retrospective analysis of the compliance officers of accounting and registration discipline and counter concealment of crimes (Journal of actual problems of jurisprudence, 2020)
This article provides a retrospective analysis of compliance by officials of criminal prosecutionaccounting and registration discipline, as well as counteraction to the shelter of criminal offenses.The purpose of this work is to study the issues of reception, registration, accounting of information aboutcriminal offenses at various stages of history (the era of slavery, the medieval period, the era of the bourgeoisie,the Soviet period, modern Kazakhstan). In addition, the aspects of compliance with accountingand registration discipline in the period of the Kazakh customary law. Also the questions of qualificationof responsibility of officials for violation of the order of consideration of information on criminal offensesare touched upon. The relevance of the study is due to the fact that in the legal literature, the retrospec tive analysis of the issues of compliance with accounting and registration discipline and counteractionto the concealment of criminal offenses is not given enough attention. The practical significance of thearticle lies in the fact that the study of historical aspects allowed to study the problems of past years,to summarize the positive experience of compliance with accounting and registration discipline by officials,as well as to identify promising areas for countering the concealment of criminal offenses. Generalscientific and private scientific research methods (historical, dialectical, comparative legal, logical) wereused in the preparation of the scientific article. The authors provides a wide range of practical examples.Key words: accounting and registration discipline, reception, registration, accounting, concealment,criminal offense.